Chicken transcriptome analysis and discovery of novel genes involved in infectious bursal disease virus infection - Ravi, Sharanya (2018)
Infectious bursal disease (IBD) is a major concern to food security because pathogenic strain of IBD virus (vvIBDV) can cause high mortality and immunosuppression in chickens that has not been controlled till date. This study aims to study the differential expression and discover novel genes in IBDV infected chickens. 18 transcriptomes generated from de novo sequencing of samples from six different lines of IBDV infected and control chicken were analysed. Sequences that did not map to the reference genome of Gallus gallus were analysed for differentially expressed genes (DEG) in IBDV infected chickens. About 600 unigenes out of 10,828 were selected for VENNTURE (Venn diagram) analysis that resulted in 12 upregulated and 18 downregulated DEGs that were common to all the six lines of chicken. Annotation predicted the functions to be involved in the transcription factor activities and extra cellular binding activities which aids in the immune response. Three upregulated and four downregulated unigenes did not have any significant BLAST hits. Gene networks generated using the weighted gene correlation network analysis (WGCNA) predicted the functions of the unknown sequences to be related to interleukin 18 binding protein, mucin13 isoform XI and extracellular matrix protein, cerebellar degenerative protein, cell surface protein, ubiquitin conjugating protein. Quantitative PCR was performed on 10 genes including the unknown genes (7 genes), FoxP3 gene and two known genes that were homologues with species other than Gallus gallus to validate the differential expression. Presence of FOX P3 gene was validated by visualizing the amplification. Based on the results, four out of seven unknown were found to be in chicken and their functional prediction contributes to the resistance against the disease.